2017
DOI: 10.3389/fmed.2017.00001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL17A in Axial Spondyloarthritis—Where Are We At?

Abstract: Knowledge regarding the mechanisms of the IL17–IL23 pathway and its role in spondyloarthritis (SpA) has been pivotal to the development of IL-17 blockade in patients with axial SpA. Previously, only anti-TNF has proven to be clinically efficacious in patients with active disease, despite non-steroidal anti-inflammatory drugs and physiotherapy. However, up to 50% fail to achieve a clinically significant response. Secukinumab, a fully humanized monoclonal antibody targeting IL-17A, has recently been approved for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
1
19
0
2
Order By: Relevance
“…Both TNF-α [ 58 ] and interleukin-17 inhibitors [ 59 ] have been shown to reduce inflammation and improve symptoms in patients with AS [ 60 ]. Furthermore, increased levels of TNF-α, IL-17, IL-23, IL-1β, and IL-6 have been found in sera and synovial fluid from AS patients [ 61 – 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both TNF-α [ 58 ] and interleukin-17 inhibitors [ 59 ] have been shown to reduce inflammation and improve symptoms in patients with AS [ 60 ]. Furthermore, increased levels of TNF-α, IL-17, IL-23, IL-1β, and IL-6 have been found in sera and synovial fluid from AS patients [ 61 – 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only other biologic currently approved for the treatment of AS is secukinumab, a monoclonal antibody directed against interleukin (IL)-17A [ 54 ]. Trials have shown the drug to be symptomatically effective compared with placebo [ 55 ].…”
Section: Tnf Inhibitorsmentioning
confidence: 99%
“…Trials have shown the drug to be symptomatically effective compared with placebo [ 55 ]. Secukinumab has not been studied in nr-axSpA, nor are there any data available on its comparative efficacy relative to TNF inhibitors [ 54 ]. At this time, the ASAS recommendations are to treat with a TNF inhibitor after failure of two NSAIDs and to use it for at least 12 weeks [ 3 ].…”
Section: Tnf Inhibitorsmentioning
confidence: 99%
“…Secukinumab, a fully human monoclonal antibody against IL-17A, is the first non-TNF-α inhibitor agent approved for AS, which opens up a therapeutic step of other cytokine targets beyond TNF (18). The benefits of secukinumab are generally seen regardless of whether patients were naive or not to TNF inhibitor therapy, and were persistent up to 5 years treatment; secukinumab was also associated with visible improvement of mobility and physical function, quality of life and work productivity in some of the trials (19).…”
Section: Immunopathogenesis Of Ankylosing Spondylitismentioning
confidence: 99%